Moderasi Hadis Suara Wanita dalam Shahih al-Bukhari - Zahroh Zahwa; Fatihunnada (Al-Manar: Jurnal Kajian Alquran dan Hadis, 2023)
Today, the role of women is increasingly broad, showing their almost equal power with men. Many women have the profession of qari'ah, preacher, lecturer, newsreader and some even become state officials. Women in this profession must raise their voices, and it is permissible to be heard by those who are not mahrams, with the condition that they do not cause slander, are not chanted or made to lull by the explanation of three hadiths in Sahih Bukhari. This study uses the library research. The results of this study concluded that women's voices are allowed to speak or be heard by the opposite sex on condition that they do not contain lust, and there are characteristics of wasathiyah related to two hadiths of women's voices.